Measuring repetitive behaviors as a treatment endpoint in youth with autism spectrum disorder. (January 2015) - Scahill, Lawrence; Aman, Michael G; Lecavalier, Luc; Halladay, Alycia K; Bishop, Somer L; Bodfish, James W; Grondhuis, Sabrina; Jones, Nancy; Horrigan, Joseph P; Cook, Edwin H; Handen, Benjamin L; King, Bryan H; et al.
Restricted interests and repetitive behaviors vary widely in type, frequency, and intensity among children and adolescents with autism spectrum disorder. They can be stigmatizing and interfere with more constructive activities. Accordingly, restricted interests and repetitive behaviors may be a target of intervention. Several standardized instruments have been developed to assess restricted interests and repetitive behaviors in the autism spectrum disorder population, but the rigor of psychometric assessment is variable. This article evaluated the readiness of available measures for use as outcome measures in clinical trials. The Autism Speaks Foundation assembled a panel of experts to examine available instruments used to measure restricted interests and repetitive behaviors in youth with autism spectrum disorder. The panel held monthly conference calls and two face-to-face meetings over 14 months to develop and apply evaluative criteria for available instruments. Twenty-four instruments were evaluated and five were considered "appropriate with conditions" for use as outcome measures in clinical trials. Ideally, primary outcome measures should be relevant to the clinical target, be reliable and valid, and cover the symptom domain without being burdensome to subjects. The goal of the report was to promote consensus across funding agencies, pharmaceutical companies, and clinical investigators about advantages and disadvantages of existing outcome measures.